Ação mutagênica in vivo e antimicrobiana do extrato hidroalcoólico de Pyrostegia venusta e seus efeitos no crescimento e diferenciação celular em um sistema eucariótico in vitro - Fernandes, Adriana Ponciano (2008)
This study analyzed the effects of the hydroalcoholic extract of Pyrostegia venusta, popularly known as cipó-de-são-joão , on various types of Gram negative and Gram positive bacteria, and on yeasts. It also evaluated the effects of the extract on the growth and cell differentiation in Herpetomonas samuelpessoai in vitro , and the in vivo mutagenic effect by the micronucleus test. The antimicrobial activity of the extract was evaluated by two methods: agar diffusion test, and tube dilution test. The growth and cell differentiation of H. samuelpessoai occurred in chemically defined medium after incubation at 28°C, for 48 hours. Growth was calculated by cell count in a Neubauer chamber, and differentiation was measured by observing cells stained by the panoptic method to calculate the percentages of the pro-, para- and opistomastigote forms. To determine the LD 50, groups of female albino Swiss mice received a single oral dose of different extract concentrations (300 mg/kg and 2000 mg/kg). For mutagenic evaluation, Swiss albino mice, aged approximately12 weeks, were used. Each trial was carried out in five groups of animals, each group consisting of 3 males and 3 females: negative control (0.9% NaCl); positive control (50 mg/kg of ENU) treatments 1, 2 and 3 (1000, 1500 and 2000 mg/kg of extract, respectively). The micronucleus test in mouse bone marrow erythrocytes was done 24 and 28 hours after treatment. The polychromatic erythrocytes (PCEs) were observed through an optical microscope and counted with the help of a digital cell counter. The results showed that the hydroalcoholic extract of Pyrostegia venusta leaves at the concentrations of 72.6 mg/mL and 145.2 mg/mL had no antimicrobial activity on the 19 strains of bacteria and yeasts tested. With regard to LD50, the extract did not show median lethal dose at the concentrations of 300 mg/kg and 2000 mg/kg. The micronucleus test showed statistically significant differences in the number/percentage index of micronucleated PCEs between the positive control group (ENU 50mg/kg) and negative control (0.9% NaCl), and positive control and extract treatments. But these differences were not observed either between the negative controls and the extract-treated group, or between the sexes and times of treatment (24 hr-48hr), thus suggesting that the hydroalcoholic extract of P. venusta leaves does not exhibit either clastogenic or aneugenic potentials.